Nutrition Education to the Community - SOEMILAH SASTROAMIDJOJO (Paediatrica Indonesiana, 1976)
The improvement of the nutritional status of the Indonesian children require an increase in food production, per capita income, level of education, better environmental hygiene, immunization and health services and nutrition education. Nutrition education is an important as an adequate food supply (by the government) and purchasing power as long as long as ignorance and superstitions concerning food are present. The importance of nutrition education is realized by the lndonesian government and is reflected in its Five Years Development Plans. Nutrition education will be emphasized and included in the program of health improvement. There should be ''educators" (in nutrition) available to make this program a success. The medical doctor, even more the pediatrician, is potentially, the right person as nutrition educator. However, the clue is that each doctor realizes the importance of nutrition education and does nutrition education, making the best use of his/her potentials.